RANCANGAN SISTEM HIDROLIK PADA FRONT ATTACHMENT ALAT PERAGA MINI EXCAVATOR - Purwanto , Sigit; Aisyah , Nyayu; Prihadianto, Braam Delfian; Krisnaputra , Radhian; Wismo , F. Eko; Bahiuddin , Irfan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
As one of the heavy equipment, an excavator is used to facilitate construction work and streamline time and energy. Hydraulic excavators are widely used in construction, mining, quarrying, and forestry applications. A hydraulic excavator is a type of heavy equipment that has several functions such as digging, loading, lifting, scraping, grading, braking, etc. One of the products which is developed by the Mechanical Engineering Department of Vocational School (SV-UGM) is the Mini Excavator. Mini Excavator has a function as excavators in general. A smaller size makes it easier to operate and apply in the field are more compact and do not require a large area. This equipment is expected to be the right teaching aid in supporting the learning process of students of the Heavy Equipment Management and Maintenance Engineering Study Program in the Mechanical Engineering Department. For the learning process to be optimal, the equipment used should be optimal. Therefore, in this research, the design and construction of the Traction Drive System for Backhoe Type Hydraulic Excavators will be carried out and some testing will also be conducted to know the performance of the mini excavator